The importance of myeloperoxidase in apocynin-mediated NADPH oxidase inhibition - Almeida, Ana Carolina de[UNESP]; Vilela, Maria Marluce dos Santos; Condino-Neto, Antonio; Ximenes, Valdecir F. (Isrn Inflammation, 2012)
Apocynin is widely used as an inhibitor of the NADPH oxidase. Since myeloperoxidase (MPO) has been considered as essential for the mechanism of action of apocynin, here we used cells with different levels of MPO and compared their sensitivity to apocynin. HL-60 cells were differentiated with DMSO or IFN γ /TNF α and compared with peripheral mononuclear (PBMC) and polymorphonuclear cells (PMN). The relative MPO activity was PBMC = HL60 DMSO < HL60 IFN γ < PMN. Apocynin inhibited the intracellular reactive oxygen species production by PMN (80%) and IFN γ /TNF α -differentiated HL-60 cells (45%) but showed a minor effect in PBMC and DMSO differentiated HL-60 cells (20%). The addition of azide decreased the efficiency of apocynin in PMN and the addition of peroxidase increased the inhibition in PBMC. We also determined the gene expression of the components gp91phox, p47phox, p22phox and p67phox in the resting cells. Apocynin did not change gp91phox, p47phox or p22phox gene expression in nonstimulated PBMC, HL60 DMSO, HL60 IFN γ /TNF α , and PMN and has a subtle increase in p67phox in HL60 IFN γ /TNF α . The results from this work suggest that a rational search for better inhibitors of NADPH oxidase in leukocytes should include a correlation with their affinity as substrates for MPO.